Influence of genetic mutations produced by irradiation with gamma-rays on the composition of starch in rice varieties (Revista Española de Fisiología, 1959)
As interesting characters of yield in the obtainance of new varieties of rice by hybridation, are usually considered the disease resistence, the prccocity, etc. The character of gelification of the starch grain is not considered, in spite of its im- portance as a primordial factor of quality.In a previous paper, we have related the organoleptic pro- prieties of somc rice varieties to physico-cheinical mesures in cióse dependence to the amylopectin and amylose contents.The possibility to obtain a great number of mutations by irradiation of different varieties, allowed us to study in the mutant generations the induced changes in the starch compo sition. This is an interesting example of the genetic influence on the biosinthesis and provides to the genetists a new critery of selection to employ it in the research of convenient hybridations.Five varieties have been submited to 3000, 5000, 7000, 15000 and 50000 reps of irradiation. In the generation XT of each sample have been studied the induced variations in amy- lose-amylopectine, in respect to the original strain, by means of spectrophotometric and absorption methods, according to the small size of the obtained samples. The irradiation with 50000 reps produced the sterility of the seeds. With the other intensities, the.morphological mu tations as well as the biochemical ones, in all the variations, showed be by chance.